Missed Opportunity or Inevitable Failure? The Search for Industrialization in Southeast Europe 1870-1940 - Michael Kopsidis (European Historical Economics Society (EHES), 2012)
Southeast Europe's countries are often denominated as the 'first developing nations'. Since the end of the 19th century the question of industrialization dominated public economic debates in Romania, Bulgaria, Greece, and later on Yugoslavia. However, despite all soaring rhetoric no sustained industrial spurts occurred before 1940. Still today the failure of industrialisation in Southeast Europe is fiercely debated in economic history. Some researchers argue that inherently backward 'Balkan peasant societies' were incapable to modernize. Others emphasize unfavourable external conditions which hindered industrialisation. The paper argues in favor of external reasons without neglecting the partial failure of native elites.ngs of industrialization, which set in during the third quarter of the nineteenth century.
Keywords: 330